2020
DOI: 10.1029/2019jc016033
|View full text |Cite
|
Sign up to set email alerts
|

A Census of the Warm‐Core Rings of the Gulf Stream: 1980–2017

Abstract: A census of Gulf Stream (GS) warm‐core rings (WCRs) is presented based on 38 years (1980–2017) of data. The census documents formation and demise times and locations, and formation size for all 961 WCRs formed in the study period that live for a week or more. A clear regime shift was observed around the Year 2000 and was reported by a subset of authors (Gangopadhyay et al., 2019, https://doi.org/10.1038/s41598-019-48661-9). The WCR formation over the whole region (75–55°W) increased from an average of 18 per y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 57 publications
2
34
1
Order By: Relevance
“…When WCR survival probabilities were compared between the two regimes, we found that the survival of WCRs has decreased from the previous regime (1980–1999) to the later regime (2000–2017). This result agrees with the reduced mean lifespan median values of WCRs in Regime 2 (see Gangopadhyay, Gawarkiewicz, Silva, et al, 2020, Tables 3 and 4). Two factors might have led to this result.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…When WCR survival probabilities were compared between the two regimes, we found that the survival of WCRs has decreased from the previous regime (1980–1999) to the later regime (2000–2017). This result agrees with the reduced mean lifespan median values of WCRs in Regime 2 (see Gangopadhyay, Gawarkiewicz, Silva, et al, 2020, Tables 3 and 4). Two factors might have led to this result.…”
Section: Discussionsupporting
confidence: 86%
“…Within the GIS data frame, an analyst examined each chart following the WCR formation, continuity, and dissipation rules. A new ring formation is documented in three situations: (i) a typical GS crest forming a closed anticyclonic vortex and detaches from the stream in the slope water; (ii) an anticyclonic eddy forms off of another large anticyclonic eddy in the slope water; and (iii) an anticyclonic eddy further away from the stream coming into the domain through Zone 4 (Gangopadhyay, Gawarkiewicz, Silva, et al, 2020). The demise of a ring is decided when a ring was last documented (or seen) in the JC charts.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations